Enhancing affective domain in training science based teachers: towards an Islamic approach - Berghout, Abdul Aziz (IIUM Press, International Islamic University Malaysia, 2012)
This paper investigates the role of affective domain in teacher and science education from an Islamic perspective. Affective domain constitutes an integral part of the general framework and theories of teacher and science education; in designing the philosophy and objectives of teacher and science education, emphasis is placed on its importance and role in the education of both teachers and learners in science, engineering and ICT based disciplines. However, in practice, there is often some confusion as to what and how the affective domain component should be envisioned, implemented, and taught. This paper advances the Islamic framework for the development of a fundamental and comprehensive approach to the integration and implementation of affective domain in teacher and science education. It analyses the articulation of values, ethics, worldview, belief system and affective aspects of the teacher’s and the learner’s personality. The paper concludes that the role of affective domain in teacher and science education from an Islamic perspective is not only important but also provides an integrated guiding approach to the development of the cognitive, psychomotor and behavioral dimensions of the learner.